Malaikat dalam Perspektif Al-Qur'an(Kajian Komparatif Penafsiran al-'abardan Quraish Shihab) - Abdul Rouf (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This study aims to examine the angels in the perspective of the Qur'an (Comparative Study of the interpretation of al-á¹¬abarÃ® and Quraish Shihab). This type of research is library research with a qualitative descriptive approach. The data collection method is a documentary, while the data analysis method uses inductive, deductive and comparative methods. The results show that al-á¹¬abarÃ® is one of the commentators who offers a method of interpretation of bi al-Ma'á¹¡È—r with the narrative approach of the Companions, and tÃ¢bi'Ã®n, interpretation of angels tends to refer to Isriliyat. This can be seen from the interpretation which says that in essence angels and demons are a group of people in heaven. Devil used to be named â€˜AzÃ¢zÃ®l. While Quraish Shihab is one of the commentators who emphasizes bi al-ra'y interpretation patterns with the language analysis approach. According to the Quraish Shihab, that istiá¹¡nÃ¢â€™ 'in the word illÃ¢ IblÃ®s is istiá¹¡nÃ¢ â€œwhich is munqaá¹iâ€ so that the word